Stem cell technology in breast cancer: current status and potential applications - Chiotaki R (Dove Medical Press, 2016)
Rena Chiotaki, Hara Polioudaki, Panayiotis A Theodoropoulos Department of Biochemistry, School of Medicine, University of Crete, Heraklion, Greece Abstract: Breast cancer, the leading cause of cancer among females, is supported by the presence of a rare subset of undifferentiated cells within the tumor, identified as breast cancer stem cells (BCSCs). BCSCs underlie the mechanisms of tumor initiation and sustenance and are implicated in the dissemination of the primary tumor to metastatic sites, as they have been found circulating in the blood of breast cancer patients. The discovery of BCSCs has generated a great amount of interest among the scientific community toward their isolation, molecular characterization, and therapeutic targeting. In this review, after summarizing the literature on molecular characterization of BCSCs and methodologies used for their isolation, we will focus on recent data supporting their molecular and functional heterogeneity. Additionally, following a synopsis of the latest approaches for BCSC targeting, we will specifically emphasize on the therapeutic use of naïve or engineered normal stem cells in the treatment of breast cancer and present contradictory findings challenging their safety. Keywords: breast cancer stem cells, cancer stem cell heterogeneity, targeting cancer stem cells, circulating tumor cells, stem cell technology